2016
DOI: 10.1111/ctr.12790
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A pharmacogenetics and tacrolimus disposition in adult heart transplant recipients

Abstract: Combined CYP3A genotype was associated with tacrolimus drug disposition in adult heart transplant recipients, but the effect was largely driven by CYP3A5*3. These data suggest that CYP3A4*22 and combined CYP3A genotypes are unlikely to provide additional information beyond CYP3A5 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…Consistent with what has been reported in solid organ transplant populations, we found that recipients with rapid-metabolizing CYP3A genotypes require higher doses of tacrolimus to maintain therapeutic drug levels compared to other genotypes. 7,11,[28][29][30][31][32][33][34][35] Rapid-metabolizing genotypes were associated with increased time to therapeutic tacrolimus level and decreased days in therapeutic range. Additionally, we found decreased rates of acute cellular rejection in lung allograft recipients with ABCB1 poor efflux activity.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with what has been reported in solid organ transplant populations, we found that recipients with rapid-metabolizing CYP3A genotypes require higher doses of tacrolimus to maintain therapeutic drug levels compared to other genotypes. 7,11,[28][29][30][31][32][33][34][35] Rapid-metabolizing genotypes were associated with increased time to therapeutic tacrolimus level and decreased days in therapeutic range. Additionally, we found decreased rates of acute cellular rejection in lung allograft recipients with ABCB1 poor efflux activity.…”
Section: Discussionmentioning
confidence: 99%
“…patients, but the effect was largely driven by CYP3A5*3. 29 Genetic polymorphisms of metabolising enzymes and transport proteins should be investigated for the individualisation of tacrolimus dosing for cardiac transplant patients in further prospective studies. In summary, the well-known covariates POD, WZ capsules and BW were successfully identified as the important factors affecting tacrolimus CL/F and V/F in heart transplant patients.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…In addition, many reports suggest that CYP3A5 is related to the mean concentration/dose ratio (C/D) of CNIs. Some researchers have reported that nonexpressers exhibit greater renal CNI metabolism; thus, even though nonexpressers require a lower initial dose, they have higher CNI blood concentrations and C/D values [51][52][53][54][55]. These results suggest that expressers experience the increased metabolic clearance of TAC and low trough concentrations, which results in a high incidence of acute rejection.…”
Section: Biomarkersmentioning
confidence: 99%